ETIK DAN EMIK PADA KARYA ETNOGRAFI - Rawa - El Amady (Universitas Andalas, 2014)
Important lesson of the two in the ethnographic work even when doing ethnographic research, ethics and emic is not a separate thing. Both are an integral part in the research process as well as in his writing. So, in an ethnographic work could not leave ethics, or leave emic, but they must appear in accordance with periodesasinya respectively